Approval plans and academic libraries : an interpretive survey - McCullough, Kathleen; Posey, Edwin D. ;Pickett, Doyle C. (Phoenix, Arizona : Oryx Press, 1977)
Approval plans are an established method for the acquisition of books and have been made a part of many academic libraries' acquisitions programs. This study of approval plans was undertaken for two reasons: primarily, to try to determine the state of the art and degree of acceptance among academic libraries and, secondarily, to compare Purdue's experience with that reported by others. The investigators comprise an acquisitions librarian, an academic librarian, and a vendor's representative.
Summary of Results -- Survey Results and Discussion -- Author's Responses -- Afterword.
Includes bibliographical references.
Keywords: ACADEMIC LIBRARIES